2011
DOI: 10.5194/hess-15-1537-2011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of climate change on the stream flow of the lower Brahmaputra: trends in high and low flows based on discharge-weighted ensemble modelling

Abstract: Abstract. Climate change is likely to have significant effects on the hydrology. The Ganges-Brahmaputra river basin is one of the most vulnerable areas in the world as it is subject to the combined effects of glacier melt, extreme monsoon rainfall and sea level rise. To what extent climate change will impact river flow in the Brahmaputra basin is yet unclear, as climate model studies show ambiguous results. In this study we investigate the effect of climate change on both low and high flows of the lower Brahma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(53 citation statements)
references
References 24 publications
3
50
0
Order By: Relevance
“…The increment in peak flow in the monsoon season is likely to be greater for moderate events and smaller for extreme events with higher return periods. Gain, Immerzeel, Sperna Weiland, and Bierkens (2011) indicated that there will be a strong increase in peak flows, both in size and frequency, although dry-season conditions are likely to increase.…”
Section: The Brahmaputra Basinmentioning
confidence: 99%
“…The increment in peak flow in the monsoon season is likely to be greater for moderate events and smaller for extreme events with higher return periods. Gain, Immerzeel, Sperna Weiland, and Bierkens (2011) indicated that there will be a strong increase in peak flows, both in size and frequency, although dry-season conditions are likely to increase.…”
Section: The Brahmaputra Basinmentioning
confidence: 99%
“…This decrease in melt water was estimated by Immerzeel and van Beek (2010); even though rainfall is projected to increase, they . By the end of the century, however, both mean and extreme discharges are consistently projected to increase in the low-lying Brahmaputra (Gain et al 2011). Estimates for Bangladesh due to projected increases in precipitation range between increases of 13 % (Masood et al 2015) up to 39 % (Darby et al 2015), compared to their respective reference periods both within the years 1980-2000 (Table 1B).…”
Section: Synthesis Of Reported Parameter Values: Future Statementioning
confidence: 99%
“…This study is focused on the CSD related to the discharge in the lower Yarlung Zangbo River Basin, which belongs to the Qinghai-Tibet Plateau where the hydrological impact of climate change is expected to be particularly strong (Immerzeel et al, 2010;Gain et al, 2011). The major meteorological stations of the lower Yarlung Zangbo River are in the eastern and central Tibet in which long-term observed records (precipitation and temperature) are available through the China Meteorological Administration (http://www.cma.gov.cn/en/).…”
Section: Study Areamentioning
confidence: 99%